2019
DOI: 10.1017/s0954579419001160
|View full text |Cite
|
Sign up to set email alerts
|

Morality in autism spectrum disorder: A systematic review

Abstract: Moral reasoning and decision making help guide behavior and facilitate interpersonal relationships. Accounts of morality that position commonsense psychology as the foundation of moral development, (i.e., rationalist theories) have dominated research in morality in autism spectrum disorder (ASD). Given the well-documented differences in commonsense psychology among autistic individuals, researchers have investigated whether the development and execution of moral judgement and reasoning differs in this populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 92 publications
(262 reference statements)
0
24
0
Order By: Relevance
“…Takeda et al, 2007; Zalla et al, 2011). Researchers have investigated whether the development and execution of moral judgement and reasoning differs in this population compared with neurotypical individuals (for a review, see Dempsey et al, 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Takeda et al, 2007; Zalla et al, 2011). Researchers have investigated whether the development and execution of moral judgement and reasoning differs in this population compared with neurotypical individuals (for a review, see Dempsey et al, 2019).…”
mentioning
confidence: 99%
“…Relying on traditional definitions of empathy and rationalist theories of morality would suggest delayed or atypical moral development among autistic individuals. However, a recent systematic review of moral psychology in autism (Dempsey et al, 2019) suggested that only minor differences in moral psychology exist between autistic and neurotypical individuals. In particular, moral judgement, that is, determining whether transgressors were morally right or wrong in their actions, was shown to be generally similar between autistic and neurotypical individuals (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that the ability to infer and base moral judgments on intentionality may be still present in ASD individuals, and potentially explains why we did not observe a between-group difference of rTPJ in representing social reputation in our task. It has also been proposed that the method of inferring intentionality differs between autistic and neurotypical participants (Dempsey et al, 2019). Here, a reduced rTPJ representation similarity in ASD, unique to the moral context, explains that patients excessively consider the negative consequences of an immoral action.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to consider intentions when judging moral culpability has been a key focus in research on morality in autism, wherein subtle differences have often been construed as deficits (for review see . However, such research has not shown robust connections between commonsense psychology and moral judgments among autistic individuals (for review see Dempsey et al, 2019). As such, autistic individuals appear to use heuristics for making moral judgments that rely less heavily on commonsense psychology than seen in neurotypical individuals, presenting a challenge to the single developmental pathway to moral maturity posited by rationalist accounts.…”
Section: Introductionmentioning
confidence: 99%